PENGARUH PEMBERIAN JENIS PAKAN TERHADAP PERTUMBUHAN DAN PERKEMBANGAN OOSIT CALON INDUK IKAN KERAPU BEBEK GENERASI KE DUA (G-2) - Tridjoko (Universitas Hang Tuah, 2021)
Humpback grouper (Cromileptes altivelis) is one of the export fisheries commodities with high economic value in the Asian market, especially Hong Kong and Singapore. Seeing that the fishing intensity is increasing, it is suspected that it has threatened the sustainability of the population in nature. This study aims to determine the effect of the type of feed on the growth and development of gonads of the second derivative humpback grouper broodstock (G-2). The individuals used were G-2 grouper fish with a weight range of 350-370 g / fish and a total length of 28,2 - 29,2 cm. The tank used is a round fiber tank with a volume of 500 l, each of which is filled with 7 humpback grouper fish. The treatments were: (A) dry pellet feed; (B) fresh feed and (C) mixed feed between dry pellets and fresh fish. Each treatment was repeated 3 times. The results showed that the feeding effect of fresh feed could stimulate the development of oocyte of the second generation of humpback grouper broodstock. The best weight growth was in treatment (B) with an average weight of : 622.4 ± 0.6 g. the largest oocyte diameter was in treatment (B) : 423.3 ± 2.9 μm.